Ecotourisme et parcs naturels : innovations et contradictions sud-africaines, le cas de HIP (Hluhluwe-Imfolozi Park) - Fabrice Folio; Anaëlle Derroisne (EchoGéo)
As one of the oldest game reserves in austral Africa, the Hluhluwe-Imfolozi Park (HIP), set in the heart of the KwaZulu-Natal province, has become a south-african example as a conservation sanctuary involved in ecotourism practices. Its rich biodiversity has paved the way to protection, tourism and participation initiatives during its development. Located in a country, which also gave priority to the sustainable/responsible tourism issues (in relation to its rich potential, level of services as well as strong governmental policy), the results are not free from several fragilities and insufficiencies. One also has to relate these facts to the inherited national socio-economical stakes. Finally, the particularity of HIP led in a mixed of seducing and, in such way, ambiguous ecotourism reality, putting together a strong and old provincial conservation programme, a diversified and adaptable tourism activity as well as a gradual involvement from the nearby tribal authorities in the Park policy.